Body composition in long-standing juvenile dermatomyositis: associations with disease activity, muscle strength and cardiometabolic measures. (29th October 2021) - Witczak, Birgit Nomeland; Bollerslev, Jens; Godang, Kristin; Schwartz, Thomas; Flatø, Berit; Molberg, Øyvind; Sjaastad, Ivar; Sanner, Helga
Abstract: Objective: To compare body composition parameters in patients with long-standing JDM and controls and to explore associations between body composition and disease activity/inflammation, muscle strength, health-related quality of life (HRQoL) and cardiometabolic measures. Methods: We included 59 patients (median disease duration 16.7 y; median age 21.5 y) and 59 age- and sex-matched controls in a cross-sectional study. Active and inactive disease were defined by the PRINTO criteria. Body composition was assessed by total body DXA, inflammation by high-sensitivity CRP (hs-CRP) and cytokines, muscle strength by the eight-muscle manual muscle test, HRQoL by the 36-item Short Form Health Survey physical component score and cardiometabolic function by echocardiography (systolic and diastolic function) and serum lipids. Results: DXA analyses revealed lower appendicular lean mass index (ALMI; reflecting limb skeletal muscle mass), higher body fat percentage (BF%) and a higher android fat:gynoid fat (A:G) ratio (reflecting central fat distribution) in patients than controls, despite similar BMI. Patients with active disease had lower ALMI and higher BF% than those with inactive disease; lower ALMI and higher BF% were associated with inflammation (elevated monocyte attractant protein-1 and hs-CRP). Lower ALMI was associated with reduced muscle strength, while higher BF% was associated with impaired HRQoL. Central fat distribution (higher A:G ratio) was associated with impaired cardiac function and unfavourable serum lipids. Conclusion: Despite normal BMI, patients with JDM, especially those with active disease, had unfavourable body composition, which was associated with impaired HRQoL, muscle strength and cardiometabolic function. The association between central fat distribution and cardiometabolic alterations is a novel finding in JDM.